CHARACTER EDUCATION AS THE FOUNDATION OF QUALITY LEADERS IN INDONESIA - Retno Irawati; Istiana Hermawati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Character education plays a crucial role in shaping ethical and high-quality leadership in Indonesia. This study explores the impact of character education on leadership quality using a qualitative method based on a literature review. The findings show that the integration of character education into leadership development programs significantly strengthens moral awareness, accountability, and commitment to public service among leaders. These results emphasize the importance of incorporating character values into educational curriculum to develop visionary and ethical leaders who can face the nation's future challenges. The study also highlights the need to integrate local cultural values, such as cooperation, tolerance, and deliberation, in leadership education to foster leaders who are not only skilled but also sensitive to societal needs. The implications of these findings are significant for policymakers and educators in developing leadership programs that prioritize ethical and culturally relevant character education.